Convective Drying with the Application of Ultrasonic Pre-Treatment: The Effect of Applied Conditions on the Selected Properties of Dried Apples - Ewa Jakubczyk; Katarzyna Rybak; Dorota Witrowa-Rajchert; Artur Wiktor; Rafał Rąbkowski; Małgorzata Nowacka (Foods)
The aim of this study was to evaluate the effect of ultrasound used as a preliminary treatment and drying temperature on the properties of dried apples (var. Golden Delicious). The aim of the work was also to optimise the process in terms of reducing the drying time and obtaining a product with specific properties. The apple tissue was sonicated for various times from 30 to 60 min. Then, the tissue was air-dried with a constant air flow of 55 to 85 °C. The work determined the dry substance content, water activity, colour parameters, content, antioxidant activity, and hygroscopicity of the dried material. The drying kinetics were also analysed. The results showed that the decrease in sonification time increased the dry matter content and reduced water activity. Also, the decrease in drying temperature caused a smaller intake of water and led to a lower hygroscopicity of dried apples. The selected parameters of the process had a positive effect on the preservation of bioactive compounds and led to an increase in antioxidant activity. Experimental results were adapted by a second-order polynomial model, where analysis of variance was utilized to define optimal drying conditions. Therefore, considering the shortest drying time, the lowest colour difference, ΔE, and the highest antioxidant activity, the best condition for the drying of apple tissue can be obtained with the application of 30 min of samples sonication and drying of apples at a temperature of 80.9 °C.